Direct test of time reversal invariance violation in B-mesons - Alvarez, Ezequiel (2008)
In this letter we reinterpret and reanalyze the available data of the B-meson factories showing the existence of direct experimental evidence of time reversal invariance violation in B-mesons. This reinterpretation consists of using the available observables to define a new observable which, in a model-independent way and without assuming CPT invariance, compares a transition between a B0 and a here-defined Bα-state, with its time reversed transition. The observable then offers a direct way to probe time reversal invariance and it is therefore independent of any conclusion obtained from current experimental information on CP violation and CPT invariance. As far as we are concerned, this is the first direct evidence of time reversal invariance violation in B-mesons and also the first one obtained from decaying particles whose mean lifetime difference is negligible. © 2008 World Scientific Publishing Company.